The games do count : America's best and brightest on the power of sports - Kilmeade, Brian (New York : ReganBooks, 2004)
Some of America's leading celebrities, politicians, and businesspeople offer personal accounts of how a love of sports and their participation in a variety of sports shaped and influenced their lives.
Tony Danza -- Jon Stewart -- Pat Croce -- Tony Robbins -- Geraldo Rivera -- Catherine Crier -- John Tesh -- Oliver North -- Gerald Ford -- George Allen -- George H. W. Bush -- Harold Ford Jr. -- Pat Williams -- George Will -- Henry Kissinger -- Jack Welch -- James Brown -- J.C. Watts -- Bill O'Reilly -- Jon Bon Jovi -- William Cohen -- Howard Schultz -- Roger Ailes -- Denis Leary -- Molly Culver -- Ron Reagan on his father, Ronald Reagan -- Rom Ridge -- Burt Reynolds -- Ray Kelly -- David Dreier -- Gray Davis -- Peter Pace -- Henry Kravis -- Bob Kerrey -- Hannah Storm -- Joe Biden -- Flight 93 (Dave Kupiecki on his friend, Mark Bingham ; Lloyd Glick on his son, Jeremy Glick ; Doug MacMillan on his friend, Todd Beamer ; Deena Burnett on her husband, Tom Burnett) -- Dennis Hastert -- Michelle Lombardo -- Robert Shapiro -- Jake Steinfeld -- Emme -- John Irving -- David Hunt -- Steve Doocy -- Condoleezza Rice -- E.D. Hill -- Kevin Sorbo -- Sean Hannity -- Robin Williams -- John Kerry -- Joan Lunden -- David Pottruck -- Carol Alt -- Ken Wolfe -- Bernie Mac -- Jim Caviezel -- John McCain -- Hank Paulson -- Kurt Russell -- Ron Shelton -- Donna Lopiano -- Laurie Dhue -- Darius Rucker -- Donald Trump -- Jerry Bruckheimer -- Melissa Payner-Gregor -- George W. Bush -- Kim Alexis -- Brian Kilmeade.
Keywords: Sports; Interviews -- United States